PENGARUH NON PERFORMING FINANCING TERHADAP PROFITABILITAS PADA PT. BANK MUAMALAT INDONESIA, TBK - Khristina Sri Prihatin; Unan Wiyanto (FKIP, Universitas Banten Jaya, 2020)
The purpose of this research were to determine the bank level of bank health toward profit at Bank Muamalat Indonesia, tbk. In banking, the non performing was the important part of bank performance achieving. The analysis technique used to see the effect of non performing finanching on profitability at PT Bank Muamalat Indonesia, Tbk is a quantitative method that uses SPSS calculation.Partial t test result, obtained t value of 9,050 with a significant level of 0,012 means that non performing finanching has a significant effect in increasing profitability.The result of this research showed that non performing finanching could influence the profitability because according to the result non performing finanching have the value up to 5%, it showed the profitability value especially the return on assets and the return on equity value that its result is under the standard value based on Indonesia Bank is ROA as much 1,25 % and ROE as much 5%.